The first record ofCoenosia attenuata Stein, 1903 (Diptera, Muscidae) from the Neotropical region (Bollettino di zoologia agraria e bachicoltura, 2024)
The predatory efficiency of the Old World "hunter fly", Coenosia attenuata, onseveral species of insect pests justifies its use as a biocontrol agent in greenhouses.The records of Coenosia attenuata from Ecuador and Pem reported here are thefirst from the Neotropical Region.
Keywords: Coenosia attenuata; Muscidae; Neotropic; biological control